The chocolate challenge - Benedis-Grab, Daphne (New York : Scholastic Inc., 2018)
Every year, Scottsdale's two elementary schools compete to see who can sell more bars of the Fantastic Five, special chocolate bar flavors available only once a year. Winning's a really big deal --and Deerfield Elementary always wins. This year, though, Granville Elementary is determined to level the playing field, even if it means making up some new rules of their own. Co-captains Phoebe and Evan are sure that their creative new sales strategy --mixed with some ingenious pranks-- will earn them the sweet taste of success. But rival captains Gabe and Julie have a dangerous competitive streak, and they're allergic to the idea of coming in second. Can the two teams sell more chocolate bars than ever before --or is the Chocolate Challenge headed for a total meldown?
Keywords: Chocolate -- Fiction; Schools -- Fiction; Competition (Psychology) -- Fiction